The respiratory distress syndrome of the newborn : studies of blood gases and acid/base balance with the object of formulating principles of treatment - Warley, Mogamat Arashat (Department of Medicine, 2020)
Respiratory failure accounts for a large, if not the largest, percentage of deaths during the first 48 hours of life. During the last ten years a great deal of research has been devoted to this early respiratory failure. The syndrome has been known by different names at different times; hyaline membrane disease (because pulmonary hyaline membrane is a frequent autopsy finding), congestive pulmonary failure, vernix membrane disease, pulmonary syndrome, and more recently the respiratory distress syndrome. A vast literature on the subject has accumulated. Many new and interesting facts have come to light and although many new theories have been put forth to explain the syndrome, the cause is still unknown.